Syntheses of Oxazolidinone-2,3-Fused Indoline and Azaindoline Derivatives - Yamada, Koji; Ishizawa, Kaho; Oonishi, Yoshihiro; Sato, Yoshihiro; Nishi, Takahide (Synlett, 2023)
We herein describe a practical synthetic method to access oxazolidinone-2,3-fused indoline and azaindoline derivatives via one-pot cyclization. These derivatives, which contain sp3-hybridized carbons, may be useful as new scaffolds in medicinal chemistry.
Keywords: 3-bromo-2-hydroxy-1-tosylindoline; 3-bromo-2-hydroxy-1-tosylazaindoline; oxazolidinone; isocyanate; cyclization